2022
DOI: 10.1111/trf.16856
|View full text |Cite
|
Sign up to set email alerts
|

Low hematocrit reduces the efficiency of CD34+ cell collection when using the Spectra Optia continuous mononuclear cell collection procedure

Abstract: Background: CD34 + cell collection efficiency (CE) is the determining factor when calculating processed blood volume (PBV) for leukapheresis (LP).However, the factors affecting CE in the continuous mononuclear cell collection (cMNC) protocol performed by the Spectra Optia apheresis system are not well established. Study Design and Methods: We retrospectively collected the data from 147 consecutive apheresis procedures across 106 healthy donors and 27 patients completed between July 2016 and December 2020 at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…For example, a recent study identified hematocrit as a factor impacting CE, but this variable was not analyzed in the current model. 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study identified hematocrit as a factor impacting CE, but this variable was not analyzed in the current model. 37…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there may be additional clinically available data that influence CE, and therefore truncation, which are not captured in this analysis. For example, a recent study identified hematocrit as a factor impacting CE, but this variable was not analyzed in the current model 37 …”
Section: Discussionmentioning
confidence: 99%
“…33,34 We recently reported that it was difficult to form target interface for collection in low pre-apheresis Hct setting using the Spectra Optia cMNC protocol, and that pre-apheresis low Hct value had a negative impact on CD34 + CE2 when this protocol was used. 35 Previous studies reported that higher CIC counts had a positive impact on CD34 + cell yield in both autologous and allogenic PBSC collection when the predecessor cell separator system, the COBE Spectra, was used. [36][37][38] However, our data indicated that there was no correlation between CD34 + cell yield per liter of PBV and CIC counts in peripheral blood during LVL procedure.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…This is readily apparent by the optimal efficiency seen in collections with hematocrits ≥35%, 55 while hematocrits <30% lead to longer times until formation of the interface, and lower procedure efficiency and stability of the interface. 56,57 Likely, higher hematocrit is not an option in sickle cell disease patients due to viscosity concerns and in this population, the hematocrit should be targeted to be not greater than 30% to minimize complications. 58 Another benefit of improving the hematocrit before collection is that blood priming would not be needed in adult patients, and in those individuals whose lymphocyte counts are low to borderline, the higher efficiency may represent the best opportunity for collecting the greatest number of cells for product manufacture.…”
Section: Rbc Massmentioning
confidence: 99%
“…The reason for this is that red cell mass influences the stability of cell layers formed during centrifugation through the ability of RBCs to exclude water as they are packed together by centripetal forces leading to well‐defined layers. This is readily apparent by the optimal efficiency seen in collections with hematocrits ≥35%, 55 while hematocrits <30% lead to longer times until formation of the interface, and lower procedure efficiency and stability of the interface 56,57 . Likely, higher hematocrit is not an option in sickle cell disease patients due to viscosity concerns and in this population, the hematocrit should be targeted to be not greater than 30% to minimize complications 58 .…”
Section: Cell Collectionsmentioning
confidence: 99%